The reality of crisis management at the International Islamic Science University from the students' point of view - Odibat, Anas Adnan (Journal of Educational and Psychological Sciences, 2020)
The study aimed to identify the reality of crisis management in the University of Islamic Sciences from the students' point of view, and the study relied on the descriptive approach, and the study population consisted of (3500) male and female students admitted to the university, and the study sample reached (373) male and female students, who were chosen In a random way, the results showed that the average dimensions of the reality of crisis management, respectively: the reality of crisis management after its occurrence, with an average of (3.65), then the reality of crisis management before its occurrence, with an average of (3.56), and finally the reality of crisis management during its occurrence, with an average of (3.10), The results also showed the absence of statistically significant differences for the gender variable, and the presence of statistically significant differences for the variable of the academic level in favor of doctoral students, and in light of the results of the study, it recommends the necessity of holding counseling programs and workshops and giving educational lectures by the university for the direction of crises and how Dealing with it, providing a trained and qualified private team at the university for crisis management.
Keywords: Crisis Management; International Islamic Science University.